Development and Applications of Lectins as Biological Tools in Biomedical Research. Issue 2 (20th August 2015) - Dan, Xiuli; Liu, Wenlong; Ng, Tzi Bun
Abstract: As a new and burgeoning area following genomics and proteomics, glycomics has become a hot issue due to its pivotal roles in many physiological and pathological processes. Glycans are much more complicated than genes or proteins since glycans are highly branched and dynamic. Antibodies and lectins are the two major molecular tools applied for glycan profiling. Though the study of antibodies and lectins started at almost the same time in 1880s, lectins gained much less attention than the antibodies until recent decades when the importance and difficulties of glycomics were realized. The present review summarizes the discovery history of lectins and their biological functions with a special emphasis on their various applications as biological tools. Both older techniques that had been developed in the last century and new technologies developed in recent years, especially lectin microarrays and lectin‐based biosensors, are included in this account.